Induced Settlement Reduction of Adjacent Masonry Building in Residential Constructions - Abolfazl Mohafezatkar Sereshkeh; Reza Jamshidi Chenari (Civil Engineering Journal, 2017)
Many buildings and heritages are yearly damaged due to new construction plans in vicinity of them. Current engineering practice in Iran lacks unfortunately regulations to enforce the designers of new buildings to re-evaluate the structural integrity of adjacent old buildings which are prone to unacceptable induced settlement and distortions. To damage assessment of old building, deflection ratio was used for unreinforced load-bearing wall (masonry) building. In this paper some practical methods like story limits for the new buildings according to the specification of old structure, improvement of shallow foundations and increasing the embedment depth of new foundations have been studied in order to decrease the settlement and undesirable effects of adjacent constructions. Parametric studies using numerical analysis, Flac3D, have paved the way how above mentioned methods can remedy the problem. So induced consolidation settlements due to new construction in adjacent building were studied.  In conclusion, increase of admissible story of new building up to one floor by increase of embedment depth as much as one meter and three floors by using of mat foundation instead of single footing were highlighted these methods.